Physiotherapy for preterm infants in the neonatal intensive care unit using the international classification of function framework - Comuk Balci, Nilay; Takci, Sahin; Akin, Mustafa Ali (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the influence of physiotherapy programmes on early preterm infants’ activity level. Method: The prospective, randomised case-control study was conducted at the neonatal intensive care unit of Ondokuz Mayis University Hospital, Samsun, Turkey, from January 2022 to May 2023, and comprised early preterm infants born at 30 weeks of gestational age or earlier. After the infants’ vital signs stabilised, they were randomised into intervention group A and control group B. Those in group A received a one-month physiotherapy programme, while those in group B received daily standard care and positioning. Other than sociodemographic data and vital signs, variations in the infants’ height and weight were monitored. Motor skills were evaluated using the Test of Infant Motor Performance. Dubowitz Neurological Examination with cut-off score of >30.5), and the Preterm Oral Feeding Readiness Scale were noted and compared between the groups. Data was analysed using SPSS 25. Results: Of the 38 infants with mean gestational age 29.03±1.26 weeks and mean and birthweight 1299.15±318.98gm, 19(50%) were in group A: 12(63.2%) girls and 7(36.8%) boys. There were 19(50%) infants in group B; 10(52.6%) girls and 9(47.4%) boys. There was no significant intergroup difference at the baseline (p>0.05). There was a significant improvement in motor skills, neurological development and feeding readiness in group A compared to group B (p=0.00). No significant intergroup differences were observed with respect to the length of stay under intensive care, respiration rate, heart rate, body temperature, oxygen saturation, body weight on the evaluation day, body weight at discharge, and head circumference at discharge (p>0.05). Conclusion: Physiotherapy in the neonatal intensive care improved motor, neurological and feeding outcomes in preterm infants. Key Words: Early intervention, Preterm infants, Motor skills, Neonatal intensive care units.